Effects of an artistic gymnastics program on the motor development of school children aged 6 to 11 years with a diagnosis of ADHD. (Revista horizonte, 2014)
The objective of this research was to analyze the effects of a program of artistic gymnastics in the motor development of children with a diagnosis of ADHD. Under a design studied quasi experimental, descriptive and comparative data from a quantitative methodology. The sample was selected under a criterion not probabilistic whereas 60 children from 6 to 11 years divided into three groups of 20 agreements to children with ADHD diagnosis and implementation of gymnastics program, ADHD without gymnastics and children without ADHD program or program of gymnastics as a control group. Students were included after signing an informed consent from parents and proceeding according to the Declaration of Helsinki, excluding those children who had voluntary retirement of research. Motor development scale (MDS) of pink net scale was used for the obtaining of motor development. Results show significant differences (p < 0.05) in the motor development of the three groups of both motor thin, global mobility, balance, body schema, temporal, and spatial organization, significant differences (p < 0.05) post program of artistic gymnastics in the motor development of children with ADHD. In conclusion, the implementation of a program of artistic gymnastics could be considered a useful tool in the approach to disorders of motor development in children with hyperactivity.